FACTORS INFLUENCING STUDENTS’ SATISFACTION ON STREET FOOD: AN EMPHASIS ON CLEANLINESS AND HEALTHINESS - Nabila Huda Akmal Nizam; Wan Hayati Wan Bujang; Firdaus Ahmad Fauzi; Norliana Hashim; Zubaidah Mohd Ali Tan (International Journal of Accounting, Finance and Business, 2022)
Street food had been the selection of foods among students’ population in higher educational institutes all over the country. There is an estimated population of 1.32 million students who currently pursued their tertiary education in Malaysia. (Education & Services, 2021). As street foods has the characteristics of affordable prices, fast services, ready to pick up, and easily accessible, they became the favorite selection for the students. However, many recent studies have confirmed that health issues among university students were related to the consumptions of street foods. Hence, the study aims to explore on the matter of cleanliness and healthiness factors which have influenced students’ satisfaction concerning their street food experiences. Respondents comprised of students of Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Pulau Pinang Kampus Permatang Pauh. Quantitative designs were employed, and responses were gathered using online survey methods. Data were analyzed using SPSS, focusing on descriptive analysis and correlational study. The researcher found that cleanliness and healthiness have the positive relationship toward students’ satisfaction on street food consumption.